Assessing the shape symbolism of the taste, flavour, and texture of foods and beverages - Spence, C; Ngo, M (BioMed Central, 2012)
Consumers reliably match a variety of tastes (bitterness, sweetness, and sourness), oral-somatosensory attributes (carbonation, oral texture, and mouth-feel), and flavours to abstract shapes varying in their angularity. For example, they typically match more rounded forms such as circles with sweet tastes and more angular shapes such as triangles and stars with bitter and/or carbonated foods and beverages. Here, we suggest that such shape symbolic associations could be, and in some cases already are being, incorporated into the labelling and/or packaging of food and beverage products in order to subconsciously set up specific sensory expectations in the minds of consumers. Given that consumers normally prefer those food and beverage products that meet their sensory expectations, as compared to those that give rise to a ‘disconfirmation of expectation’, we believe that the targeted use of such shape symbolism may provide a means for companies to gain a competitive advantage in the marketplace. Here, we review the latest research documenting a variety of examples of shape symbolism in the food and beverage sector. We also highlight a number of the explanations for such effects that have been put forward over the years. Finally, we summarise the latest evidence demonstrating that the shapes a consumer sees on the label and even the shape of the packaging in which the product is served can all impact on a consumer’s sensory-discriminative and hedonic responses to food and beverage products.